Analysis of the Administrative Experiences of the Brazilian Federations in the Consolidation Program of the National Pact for Water Management (PROGESTÃO) - Almeida, Bianca Maria Jacinto de; Fontana, Marcele Elisa; Almeida, Natallya Levino de (Management & Public Policies Journal, 2023)
PROGESTÃO is a financial incentive program, with the principle of payment for achieving targets defined between the National Water Agency and the federations of Brazil, which has taken on the task of promoting water resources public management in the country. However, federations often do not reach the established targets. Understanding the problems is essential to structure decision-making processes in order to improve processes. Thus, through document analysis, the recurring problems of non-compliance with the program's targets were surveyed. Based on this diagnosis, specialists in the area of water resources were consulted and mitigation actions were proposed for each problem. This work contributes to the joint analysis, helping public managers in proposing policies and actions aimed at making the program more efficient.